2021
DOI: 10.36713/epra8524
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of English Tweets Using Bigram Collocation

Abstract: Community and portal websites like Twitter, Facebook, Tumbler, Instagram, and LinkedIn etc. have significant impact in our day-to-day life. One of the most popular micro-blogging platforms is twitter that can provide a huge amount of data which in future can be used for various applications of opinion mining like predictions, reviews, elections, marketing etc. The users use this platform to share their views, express sentiments on various events of their daily life. Previously, many researchers have worked wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Wolk et al [5] have demonstrated the efficiency of sentiment-based comment text classification and depression detection based on call-gram analysis and the deep model BERT of the language representation, while Moyeen et al [11] note that bigram-based vectorization considerably increases the quality of classification, in contrast to the use of trigrams, and so the study of the authors was aimed at identifying bigrams and trigrams that describe the subject area and considering approaches to the vectorization of comment texts based on the analysis of bigrams and their characteristics to solve the problems of classifying and clustering comments containing a description of affective disorders.…”
Section: Survey Of Literature On Research Topicsmentioning
confidence: 99%
“…Wolk et al [5] have demonstrated the efficiency of sentiment-based comment text classification and depression detection based on call-gram analysis and the deep model BERT of the language representation, while Moyeen et al [11] note that bigram-based vectorization considerably increases the quality of classification, in contrast to the use of trigrams, and so the study of the authors was aimed at identifying bigrams and trigrams that describe the subject area and considering approaches to the vectorization of comment texts based on the analysis of bigrams and their characteristics to solve the problems of classifying and clustering comments containing a description of affective disorders.…”
Section: Survey Of Literature On Research Topicsmentioning
confidence: 99%